Endogenous YAP1 activation drives immediate onset of cervical carcinoma in situ in mice. Issue 10 (21st August 2020) - Nishio, Miki; To, Yoko; Maehama, Tomohiko; Aono, Yukari; Otani, Junji; Hikasa, Hiroki; Kitagawa, Akihiro; Mimori, Koshi; Sasaki, Takehiko; Nishina, Hiroshi; Toyokuni, Shinya; Lydon, John P.; et al.
Abstract: Cervical cancer (CC) is usually initiated by infection with high‐risk types of human papillomavirus (HPV). The HPV E6 and E7 proteins target p53 and RB, respectively, but other cellular targets likely exist. We generated uterus‐specific MOB1A/B double KO (u Mob1 DKO) mice, which immediately developed cervical squamous cell carcinoma in situ. Mutant cervical epithelial cells showed YAP1‐dependent hyperproliferation, altered self‐renewal, impaired contact inhibition, and chromosomal instability. p53 activation was increased in u Mob1 DKO cells, and additional p53 loss in u Mob1 DKO mice accelerated tumor invasion. In human CC, strong YAP1 activation was observed from the precancerous stage. Human cells overexpressing HPV16 E6/E7 showed inactivation of not only p53 and RB but also PTPN14, boosting YAP1 activation. Estrogen, cigarette smoke condensate, and PI3K hyperactivation all increased YAP1 activity in human cervical epithelial cells, and PTPN14 depletion along with PI3K activation or estrogen treatment further enhanced YAP1. Thus, immediate CC onset may initiate when YAP1 activity exceeds an oncogenic threshold, making Hippo‐YAP1 signaling a major CC driver. Abstract : We generated uterus‐specific MOB1A/B double KO (u Mob1 DKO) mice, which immediately developed cervical squamous cell carcinoma in situ. Cervical cancer (CC) onset may initiate when YAP1 activity exceeds an oncogenic threshold, making Hippo‐YAP1 signaling a major CC driver. p53 activation was increased in u Mob1 DKO cells, and additional p53 loss in u Mob1 DKO mice accelerated tumor invasion.